Identifying risk factors for osteoradionecrosis of the jaws: a systematic review and meta-analysis - Rafaella Luiza Bergamaschi de Carli; Naiara Alves Marega; Analú Barros de Oliveira; Luana Paula Borges da Costa e Silva; Túlio Morandin Ferrisse (Clinical Oral Investigations, 2026)
Abstract Objectives Osteoradionecrosis of the jaws (ORNJ) is a severe complication of head and neck radiotherapy associated with substantial morbidity. This study aimed to identify factors associated with ORNJ. Materials and methods This systematic review followed PRISMA and Cochrane guidelines. PubMed, Scopus, Web of Science, SciELO, Embase, LILACS, and the Cochrane Library were searched for observational studies on ORNJ. Clinical characteristics, risk factors, radiological findings, and risk of bias were assessed. Results Of 627 records, 27 studies were included in qualitative synthesis and 10 in meta-analysis. Computed tomography was the most frequently used imaging method, and sample selection was the main methodological limitation. Meta-analysis identified associations with smoking (OR = 2.56; p < 0.0001), post-radiotherapy dental extractions (OR = 8.38; p < 0.0001), oropharyngeal tumors (OR = 2.35; p < 0.0001), T2 stage (OR = 1.78; p = 0.0002), T4 stage (OR = 1.98; p = 0.0002), and oral cavity (OR = 4.00/ p < 0.0001); good oral hygiene was protective (OR = 0.40; p = 0.0057). Conclusion Smoking, post-radiotherapy dental extractions, oral cavity and oropharyngeal tumors, and T2 and T4 tumor stages were associated with increased odds of ORNJ, whereas good oral hygiene showed a protective effect. These findings reinforce the importance of minimizing post-radiotherapy extractions and maintaining rigorous oral hygiene in patients undergoing head and neck radiotherapy. Clinical relevance Identifying modifiable risk factors may support prevention, surveillance, and individualized management of ORNJ in patients receiving head and neck radiotherapy through integrated multidisciplinary clinical and dental care.